2020
DOI: 10.1167/iovs.61.8.34
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 Involvement in the Development of Idiopathic Epiretinal Membranes

Abstract: Purpose This work was aimed to further characterize cells of idiopathic epiretinal membranes (iERMs). We wanted to determine the contribution of 90-kDa heat shock protein (HSP90) to sustain the transforming growth factor-β (TGF-β)-mediated signal transduction pathway in iERM. Methods Immunofluorescence and confocal microscopy were carried out on deplasticized sections from 36 epiretinal membranes processed for electron microscopy and on frozen sections from five additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Idiopathic ERMs express collagens I, III, IV, and VI; fibronectin; and laminin as previously reported [17,22,23]. As far as collagen IV is concerned, the isoform detected in iERMs should be the [α1(IV)] 2 α2(IV).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Idiopathic ERMs express collagens I, III, IV, and VI; fibronectin; and laminin as previously reported [17,22,23]. As far as collagen IV is concerned, the isoform detected in iERMs should be the [α1(IV)] 2 α2(IV).…”
Section: Discussionsupporting
confidence: 73%
“…However, the variations occurring in the relationships between iERMs and the ILM received little attention [ 20 ]. The unusual technique that we employ, immunofluorescence and confocal microscopy on semithin epon-embedded sections [ 17 , 23 ], produces high-quality images that allow the study of details that probably have gone unnoticed so far. In this way, we have observed that the relationships between iERMs and their associated ILMs vary greatly: from very thin iERMs, just covering the ILM, to iERMs that, slowly gliding over the ILM, induce the latter to form large loops [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF‐β is a cytokine with important homeostatic functions in proliferation, differentiation and apoptosis 68 . Activation of TGF‐β1 triggers signal transduction pathways promoting the transcription of TGF‐β target genes needed for fibrogenesis 69 . Interestingly, myofibroblasts themselves can release latent TGF‐β that bind to ECM proteins forming a reservoir of TGF‐β, and extracellular mechanical stress transmitted by integrins induces release of TGF‐β 70 .…”
Section: Histopathology and Pathogenesismentioning
confidence: 99%